Prenatal diagnosis of VACTERL association: a case report - Tongsong T. (2014)
A prenatal diagnosis of VACTERL association, a combination of vertebral (V), anal (A), cardiac (C), tracheoesophageal (TE), renal (R) and limb (L) anomalies was made at 30 weeks of gestation, based on the sonographic demonstration of vertebral defects, bilateral renal agenesis, and left lower limb defects. Additionally, severe oligohydramnios and fetal growth restriction were also documented. After proper counseling, elective termination of pregnancy was done, resulting in a stillborn infant with multiple malformations compatible with the VACTERL association. The postnatal X-ray and autopsy revealed verterbral defects, anorectal atresia with undetermined sex, cardiac defect of ventricular septal defect, tracheal agenesis with distal atresia of esophagus, bilateral renal agenesis, and limbs defects. The chromosomal study revealed normal, 46,XY. This report emphasizes the important role of prenatal ultrasound in the diagnosis and management of this disorder.